Partial Hepatectomy for the Resistant Fasciola Hepatica Infection in a Child - Belgin, Gülhan (APSP J Case Rep, 2015)
Fascioliasis is an emerging and important chronic parasitic disease caused by two trematode liver fluke species: Fasciola hepatica (F. hepatica) and Fasciola gigantica (F. gigantica) infecting several herbivorous mammals including cattle, goats, sheep, and humans. We report a 9-year-old girl who suffered from F. hepatica infection and underwent right hepatectomy because of increasing abdominal pain resistant to anthelmintic chemotherapy. When anthelmintic drug treatment is not effective and abdominal pain persists, surgical resection including hepatectomy should be kept in mind for resistant F. hepatica infection.